Capturing Crime at the Micro-place: A Spatial Approach to Inform Buffer Size - De Biasi, Alaina (Journal of quantitative criminology, 2021)
The current study develops a methodology to identify spatially relevant buffer sizes for micro-place evaluation research. It applies this methodology in an examination of the causal impact of demolitions on crime in Detroit, Michigan.